Analisis Pekerjaan/Tugas dalam Pendidikan Islam - Oktavia, Alia; Sari, Desi Purnama; Jamilus, Jamilus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze various aspects related to work/tasks in Islamic education. The study uses a literature study (library research) approach. The data sources in this study consist of Primary Sources such as the Qur’an and hadith, and Secondary Sources such as books, journal articles, research reports, proceedings, dissertations/theses, as well as relevant academic digital sources. The selection of literature is carried out through a systematic search process in scientific databases such as Google Scholar, DOAJ, and Garuda. The analysis technique used is content analysis. The analysis results indicate that job analysis is very important and urgently needed to be implemented in schools. Identifying job specifications is crucial for teachers and all staff. The techniques or methods used to conduct a job analysis do not have to be the same in every company or school. It all depends on the organization's own needs. However, what is very important is that the results of the job analysis must be accurate and neatly recorded to serve as a reference in the subsequent human resource management process. The connection between job analysis and the human resource management process or functions is very close. Job analysis is conducted in the human resource management planning process. Then the results can be used in decision-making throughout the entire human resource management process.